2020
DOI: 10.1002/aic.16549
|View full text |Cite
|
Sign up to set email alerts
|

Acid gas adsorption on zeolite SSZ‐13: Equilibrium and dynamic behavior for natural gas applications

Abstract: In developing new adsorption separation processes, it is necessary to study both the equilibrium and dynamic adsorption properties of potential materials. Experimental determination of isotherms and dynamic breakthrough properties aid in the development of modeling new adsorption systems toward process development. Here, the equilibrium adsorption properties of a small‐pore zeolite, Na‐SSZ‐13, are studied for its natural gas separation potential. Using volumetric, gravimetric, and dynamic column breakthrough a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…[9][10][11] Liu et al synthesized desulfurization sorbent with highly dispersion of active components by combining porous MAS-9 and Ca-based oxides. 12 It was found that the sorbent exhibited a sulfur capacity of 17.16 g S 100 g -1 sorbent. Mi et al applied MCM-41 as porous supporter to promote the desulfurization performance of ZnO-based sorbent.…”
Section: Introductionmentioning
confidence: 98%
“…[9][10][11] Liu et al synthesized desulfurization sorbent with highly dispersion of active components by combining porous MAS-9 and Ca-based oxides. 12 It was found that the sorbent exhibited a sulfur capacity of 17.16 g S 100 g -1 sorbent. Mi et al applied MCM-41 as porous supporter to promote the desulfurization performance of ZnO-based sorbent.…”
Section: Introductionmentioning
confidence: 98%
“…Among the existing separation technologies, adsorption separation featuring simple operating conditions, energy saving, and high adsorption accuracy has been proved to be a potential separation technology with broad prospects for gas separation 11–13 . As an emerging advanced adsorbent, metal–organic frameworks (MOFs) are attracting more and more attention by virtue of their multifarious structural topologies, precise structural determination, and tunability of pore surface functionalities 14–16 .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the NG extracted from the oil and gas fields contains a certain amount of water. The acidic substances in NG combine with water to form an acidic solution, which will greatly reduce the transmission efficiency of gas production pipeline and corrode the pipeline 4 . Therefore, NG dehydration is one of the important operations in NG processing industry.…”
Section: Introductionmentioning
confidence: 99%
“…Gas solubility analysisThe solubility of CH4 in Tethaline, Ethaline, and Reline was predicted at 303.2-333.2 K and 0-3.5 bar by the COSMO-RS model, as shown in Figures 5-7 (see Tables S3-S5 for detailed data). It can be seen from Figures 5A-C that under the same temperature and pressure, the solubility of CH 4 gas in Tethaline decreases significantly with the Solubility of CH 4 in Reline (ChCl:Urea) with the molar ratios of 1:1.5 (A), 1:2 (B), 1:2.5 (C), and 1:2 (98 wt% Reline + 2 wt% H 2 O) (D).…”
mentioning
confidence: 99%